Plant Cell Wall Plasticity under Stress Situations - García-Angulo, Penélope; Largo-Gosens, Asier (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is focused on recent novel research related to the role of plant cell walls under biotic and abiotic stresses, which was published in the Special Issue "Plant Cell Wall Plasticity under Stress Situations" of the Plants journal. Considering the importance of this plant cell structure in a plethora of plant development processes, this book focused on unraveling the roles of different cell wall components and their turnover in plant defense against pathogens and adaptative responses, in cell wall hydration ability, and in the development of primitive water transport systems in non-vascular plants.